2014
DOI: 10.1111/hel.12115
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Arginine Decarboxylase Gene (ORF HP0422, speA) Involved in Acid Tolerance in Helicobacter pylori

Abstract: Altogether, these results provide novel information regarding the H. pylori physiology and acid response mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Among those proteins, we have identified the urease subunits UreA and UreB, Pfr, NapA, and the DNA-binding protein HU [9,10]. We have also shown that the Fur-regulated (ferric uptake regulator) arginine decarboxylase gene, speA, is overexpressed under acid stress conditions [11,12]. The speA gene is homologue to adiA from Escherichia coli, a gene that participates in the acid response system 3 (AR3).…”
mentioning
confidence: 99%
“…Among those proteins, we have identified the urease subunits UreA and UreB, Pfr, NapA, and the DNA-binding protein HU [9,10]. We have also shown that the Fur-regulated (ferric uptake regulator) arginine decarboxylase gene, speA, is overexpressed under acid stress conditions [11,12]. The speA gene is homologue to adiA from Escherichia coli, a gene that participates in the acid response system 3 (AR3).…”
mentioning
confidence: 99%
“…The HP0422 gene of H. pylori 26695 strain has been shown to encode for arginine decarboxylase . In general, biosynthetic arginine decarboxylases require PLP and the divalent Mg 2+ ion as cofactors for decarboxylation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of an annotated L‐ornithine decarboxylase gene in H. pylori 26695 strain, the pathway in which the metabolism of L‐arginine by ADC occurs, may be crucial for the synthesis of polyamines. This enzyme has also been suggested to be important for acid adaptation of the bacterium in the host . However, it has not been studied at a molecular level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations